1996
DOI: 10.1111/j.1365-2605.1996.tb00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrovasography in normal and vasectomized men before and after vasectomy reversal

Abstract: The electrical pattern of the vas deferens, or electrovasogram (EVG), was studied in 22 healthy volunteers, 20 vasectomy subjects and 18 individuals after vasectomy reversal. Their mean ages were 38.8 +/- 7.3, 44.3 +/- 7.9 and 58.6 +/- 6.6 years, respectively. Two electrodes were applied to the posterior aspect of the upper part of the scrotum. During the operation of vasectomy reversal, an electrode was applied directly to each of the two vasal segments before and immediately after vasovasostomy. The electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The current study as well as earlier studies [8,9] have shown that normally the VD, under resting conditions, discharges electric waves in the form of PPs and APs. These waves seem to be responsible for the motile activity of the VD.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The current study as well as earlier studies [8,9] have shown that normally the VD, under resting conditions, discharges electric waves in the form of PPs and APs. These waves seem to be responsible for the motile activity of the VD.…”
Section: Discussionmentioning
confidence: 79%
“…The latter is differentiated as bradyvasa, tachyvasa, or vasarrhythmia. The normal vasal electric rhythm ranges from 4.2 to 8.3 cycles/rain (cpm; mean 6.6 _+ 1.5 cpm) [9]. Bradyvasa is defined as a decrease in PP frequency to less than 2 cpm; tachyvasa, as an increase in the regular frequency to more than 10 cpm; and vasarrhythmia, as an increase in PP frequency with irregular rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations